Effectiveness of human papillomavirus vaccination in young Japanese women: a retrospective multi-municipality study - Akiko Tozawa-Ono; Masaharu Kamada; Katsuhiro Teramoto; Hitoshi Hareyama; Shoji Kodama; Tokuzo Kasai; Osamu Iwanari; Tomoe Koizumi; Nobuyoshi Ozawa; Mitsuaki Suzuki; Katsuyuki Kinoshita (Taylor & Francis Group, 2021)
In Japan, government support for human papillomavirus (HPV) vaccination began in November 2010. However, the mass media repeatedly reported on severe adverse events. The Japanese Ministry of Health, Labor and Welfare suspended proactive recommendations for HPV vaccines in June 2013. Japan's HPV vaccination rate dropped from 70% to less than 1% in 2017. We examined cervical cancer screening results in terms of abnormal cytology, histology, and HPV vaccination status among 11,903 women aged 20 to 25 y in the fiscal year 2015. The overall rate of HPV vaccination was 26.1% (3,112/11,903). Regarding cytology, the rate of atypical squamous cells of undetermined significance (ASC-US) or worse was 3.3% (103/3,112) in women who received HPV vaccination (vaccine (+) women) and 5.6% (496/8,791) in women who did not (vaccine (-) women). The rate of high-grade squamous intraepithelial lesion (HSIL) or worse was 0.26% (8/3,112) in vaccine (+) women and 0.81% (72/8,791) in vaccine (-) women. Regarding histology, the rate of cervical intraepithelial neoplasia 1 or worse (CIN1+) was 1.4% (42/3,112) in vaccine (+) women and 2.1% (178/8,791) in vaccine (-) women. The rates of CIN2+ and CIN3+ were similar regardless of vaccination. We found a significantly lower incidence of CIN in vaccine (+) women. These results suggest that the resumption of recommending HPV vaccination as primary prevention for cervical cancer is needed in Japan.